Fifty years of communicative language teaching; A synthesis of critical implementation issues - Mohd. Asraf, Ratnawati; Hossain, Muhammad Tofazzel; Tan, Kok Eng (Asian EFL Journal Press, 2019)
The last few decades have witnessed the widespread adoption of the communicative approach to teaching English to students of other languages with a view of helping them achieve communicative competence. However, in terms of implementation, Communicative Language Teaching (CLT) has encountered various problems in the EFL and ESL contexts. Drawing on previous research, this article presents the reader with a critical review and synthesis of the issues precluding the usage of CLT in ESL/EFL countries around the world. Specifically, it examines the problems faced by teachers in using the approach and the constraints resulting from their lack of skills and capability, culture, and context and examination-oriented education systems. The article concludes with an emphasis on the need to develop teachers' English language proficiency, provide regular pedagogical training in CLT, adapt the approach to be more culture and context sensitive, and create more authentic language learning assessment to overcome the wash-back effect. CLT may be looking at a better future in ESL/EFL countries if these critical issues can be addressed effectively.